Withdrawal capacity and strength of self-tapping screws on cross-laminated timber. (March 2022) - Dang Khai, Tran; Gi Young, Jeong
Abstract: The goal of this study was to investigate withdrawal capacity and strength of self-tapping screws (STSs) on cross-laminated timber (CLT). Effects of wood density, diameter, and penetration length on withdrawal behaviors of STS on CLT were evaluated. An equation was proposed to predict the withdrawal capacity of STSs on CLT. With a higher density of CLT, the withdrawal capacity and strength increased from 19.7 to 57.3%. Beneficial effects of a higher wood density of CLT on withdrawal behavior were reduced when STSs had large diameters (9 mm or 11 mm) and long penetration lengths (110 mm or 130 mm). With an increment of STS diameter from 5 mm to 11 mm, the withdrawal capacity increased from 5.7 to 27.7%, while the withdrawal strength decreased from 10.2 to 29.1%. When the penetration length was increased from 10 mm to 57 mm, the withdrawal capacity was increased significantly from 16.1 to 124.0%, whereas the withdrawal strength did not change significantly. A new format of prediction equation for the withdrawal capacity of STSs on CLT was proposed based on test results. The proposed prediction well reflected the withdrawal capacity of STSs with all test configurations, showing an average difference of 4.64% between predicted and experimental values.